Study on the impact of regional carbon emissions on enterprise technological innovation under the background of low-carbon transformation in China - Lu, Hualiang; Xie, Zhenying; Liu, Yongchun; Xu, Guangwei (Frontiers in Environmental Science, 2024)
Low-carbon transition, as the backbone of corporate innovation drive, has an important strategic position globally. In order to avoid heterogeneous intercepts related to explanatory variables or interfering with each other, this paper empirically examines the impact of regional carbon emissions on corporate technological innovation and its mechanism based on the data of listed companies in China from 2009 to 2020, using a fixed-effects model. It is found that 1) the reduction of regional carbon emissions is favourable to corporate technological innovation; 2) in terms of the impact mechanism, the reduction of regional carbon emissions promotes corporate technological innovation by enhancing R&D investment and reducing financing constraints. 3) Based on the study of heterogeneity, it is found that: from the perspective of spatial distribution, regional carbon emissions show the phenomenon of “high on both sides and low in the middle”; state-owned enterprises refer to wholly state-owned enterprises, wholly state-owned companies and state-owned capital holding companies in which the State Council and the local people’s governments respectively perform the responsibilities of funders on behalf of the state. In terms of the nature of equity, compared with state-owned enterprises, regional carbon emissions have a greater impact on the technological innovation of non-state-owned enterprises. 4) Further analysis reveals that the low-carbon city pilot policy is conducive to regional carbon emission reduction. Through the comparison before and after the implementation of low carbon policy, this paper reliably verifies that the introduction of urban carpet policy is conducive to regional carbon emissions, and explores the issue of enterprise technological innovation from the perspective of low carbon transformation, providing theoretical support for the carbon emission reduction efforts and the improvement of the technological innovation capacity of different enterprises. At the same time, it fully affirmed the important role of regional carbon emissions, continued to deepen the process of green transformation of enterprises, and boosted the high-quality development of low-carbon enterprises.